A line drawn between human and nature by homo sapiens itself - Juulius Vaiksoo 2002- (2024)
In this given research paper one can read about a research question ‘Why does human being separate itself from animal kingdom?’. The question appeared while creating a BA graduation work “naturally” (“náttúrulega” in Icelandic) at Iceland University of the Arts. The performance was choreographed by Juulius Vaiksoo, danced by Torfi Tómasson and Mari Ann Valkna. The paper consists of two main topics. Firstly, an observation on indigenous people and their deep connection to nature and secondly a discussion about a cultural person and their relationship with animal characteristics and nature. All of that is tied together with a process of the dance piece “naturally”. The paper uses largely solutions/answers that came up during rehearsal period as well as an Estonian translation of a book by Jonas Frykman and Orvar Löfgren called “Culture Builders: A Historical Anthropology of Middle-Class Life”. The research paper, as well as the performance, dwells around the same topic: What is human and what is animal?